Rationale and Design of a Randomized Controlled Trial on Intensive Management of Blood PRESSure and Cholesterol in Elderly Chinese with Hypertension and Atrial FibrillatION (IMPRESSION) - Wei Zhang; Yi Chen; Qifang Huang; Ji-Guang Wang; Tianyu Xu; Xiaoxia Fu. (Cardiology Discovery)
Abstract. Hypertension significantly increases the risk of embolic stroke and systemic embolism in patients with atrial fibrillation, while statin therapy can improve long-term outcomes in hypertensive patients at high risk. However, it is still unclear whether patients with both hypertension and atrial fibrillation can benefit from intensive management of blood pressure and cholesterol. IMPRESSION is a 3-year prospective, randomized, open-label, blinded-endpoint investigation. A total of 1200 hypertensive patients with atrial fibrillation from about 40 clinical centers nationwide will be included upon confirming the presence of both hypertension and atrial fibrillation and will be randomly assigned to groups for intensive or standard management of blood pressure and cholesterol. Patients in all groups will have office and home blood pressure measured by the end of the first month and every 3 months thereafter. The effects of blood pressure and cholesterol management strategies in patients with hypertension and atrial fibrillation on fatal and non-fatal stroke, acute myocardial infarction, and cardiovascular death at 3 years will be assessed. The IMPRESSION study protocol has received approval from the Ethics Committee of Ruijin Hospital, Shanghai Jiaotong University School of Medicine. The procedures set out in this protocol are in accordance with the principles of the Declaration of Helsinki and Good Clinical Practice guidelines. The results will be published following the CONSORT statement in a peer-reviewed scientific journal (Trial registration number: NCT04111419).